Incidence patterns of childhood non-Wilms renal tumors: Comparing data of the Nationwide Registry of Childhood Hematological Malignancies and Solid Tumors (NARECHEM-ST), Greece, and the Surveillance, Epidemiology, and End Results Program (SEER), USA. (June 2022) - Doganis, Dimitrios; Karalexi, Maria A.; Panagopoulou, Paraskevi; Bouka, Panagiota; Bouka, Evdoxia; Markozannes, Georgios; Ntzani, Evangelia E.; Steliarova-Foucher, Eva; Petridou, Eleni Th.; ,; Moschovi, Maria; Antoniad, Kondilia; et al.
Abstract: Background: We used, for the first time, data registered in the Nationwide Registry for Childhood Hematological Malignancies and Solid Tumors (NARECHEM-ST)-Greece to estimate incidence/time trends of the rare childhood (0–14 years) non-Wilms tumors (non-WT), and compared the results of malignant non-WT to those from the Surveillance, Epidemiology, and End Results Program (SEER)-USA. Methods: Fifty-five cases (n = 33 malignant-only) were extracted from NARECHEM-ST (2001–2020) and 332 malignant cases from SEER (1990–2017). To allow between-country comparisons, age-standardized incidence rates (AIR) of malignant-only non-WT were calculated, and temporal trends were evaluated using Poisson and joinpoint regressions. Results: In NARECHEM-ST, malignant and non-malignant non-WT accounted for 22.6% of all renal tumors. Among malignant tumors, the AIR was 1.0/10 6 children in Greece, similar to that calculated for SEER, USA (AIR=0.9/10 6 ). The proportion of infant malignant and non-malignant non-WT was 27% (20% before 6 months) in NARECHEM-ST. Most common non-WT in Greece were congenital mesoblastic nephromas (CMN) diagnosed mainly in infancy (CIR=7.2/10 6 ). The proportion of infant malignant non-WT was 20% in SEER (AIRinfancy =2.5/10 6 ), mainly attributed to rhabdoid tumors (CIR=1.6/10 6 ). The male-to-female (M:F) ratio of malignant non-WT was 0.9 in NARECHEM-ST vs. 1.2 in SEER, whereas boys outnumbered girls with clear cell sarcoma in NARECHEM-ST (M:F=4.0). Lastly, significantly increasing trends in incidence rates were noted in NARECHEM-ST [+ 6.8%, 95% confidence intervals (CI): 0.5, 13.3] and in SEER (+7.3%, 95%CI: 5.6, 9.0). Conclusions: Observed incidence, time trends and sociodemographic variations of non-WT may reflect differential registration practices and healthcare delivery patterns including differences regarding surveillance, coding and treatment practices. Highlights: The proportion of non-WT among all renal tumors was 22.6% in Greece. The AIR of malignant non-WT was similar in Greece (1.0/10 6 ) and SEER, USA (0.9/10 6 ). The non-WT incidence was higher during infancy than in later age in SEER, USA. There is need for common registration and coding standards and monitoring of the occurrence of these rare entities to improve quality and comparability of international data.